(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
This research aims to reveal the use of e-commerce by the Rumah BUMN Kepulauan Meranti as a sociopreneur in optimizing the utilization of sago potential. The research method used is a descriptive qualitative approach through interviews, observation, and document analysis. The research results show that social networks play an important role in helping Rumah BUMN Kepulauan Meranti to expand market reach, increase awareness of sago products, and strengthen branding as a Sociopreneur. With good cooperation with various parties, Rumah BUMN Kepulauan Meranti can optimally utilize the potential of sago so that it has a positive impact on the local community and the surrounding environment. This research provides an important contribution to understanding the importance of the role of social networks in supporting the development of E-Commerce to increase the sustainable use of sago potential.